2022
DOI: 10.1093/nar/gkac1164
|View full text |Cite
|
Sign up to set email alerts
|

Targeted bacterial conjugation mediated by synthetic cell-to-cell adhesions

Abstract: Genetic interventions on microbiomes, for clinical or biotechnological purposes, remain challenging. Conjugation-based delivery of genetic cargo is still unspecific and limited by low conjugation rates. Here we report an approach to overcome these problems, based on a synthetic bacterial adhesion system. Mating assemblers consist on a synthetic adhesion formed by the expression on the surface of donor and target cells of specific nanobodies (Nb) and their cognate antigen (Ag). The Nb–Ag bridge increased 1–3 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Interestingly, we observed a higher frequency of conjugation of pCitro-15a to C. rodentium than to other bacteria, agreeing with studies that showed specificity in the conjugation process. , A number of groups have utilized conjugative systems with broad host ranges in an attempt to access a significant fraction of the targeted microbiome for editing. While promising, low conjugation rates to diverse bacteria in the targeted microbiome and the stability of conjugative plasmids with resident plasmids are confounding factors. Bacterial resistance to Cas9-killing has also been documented and could be minimized by multiplexing sgRNAs to different targets and tighter regulation of Cas9 expression. , In many cases, conjugative systems required optimization by in vitro evolution, gene minimization, or other manipulations to enhance conjugation to desired recipients . In contrast, by tapping the natural diversity of conjugative systems optimized for specific bacterial genera, or specific species, issues such as conjugation efficiency, compatibility with resident plasmids, and stability have been evolutionary preoptimized for the microbial communities of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed a higher frequency of conjugation of pCitro-15a to C. rodentium than to other bacteria, agreeing with studies that showed specificity in the conjugation process. , A number of groups have utilized conjugative systems with broad host ranges in an attempt to access a significant fraction of the targeted microbiome for editing. While promising, low conjugation rates to diverse bacteria in the targeted microbiome and the stability of conjugative plasmids with resident plasmids are confounding factors. Bacterial resistance to Cas9-killing has also been documented and could be minimized by multiplexing sgRNAs to different targets and tighter regulation of Cas9 expression. , In many cases, conjugative systems required optimization by in vitro evolution, gene minimization, or other manipulations to enhance conjugation to desired recipients . In contrast, by tapping the natural diversity of conjugative systems optimized for specific bacterial genera, or specific species, issues such as conjugation efficiency, compatibility with resident plasmids, and stability have been evolutionary preoptimized for the microbial communities of interest.…”
Section: Discussionmentioning
confidence: 99%
“…This presents an opportunity to implement conjugation systems in which only donors are engineered. This is true, too, for mannoprotein-based adhesion between bacteria and yeasts: whereas some research has shown the benefit of engineered adhesion to conjugation among bacteria 70 , the native binding strategy employed in this work avoids the need to engineer recipient cells while allowing further options for engineering donors, e.g. by making the bacterial binding mechanism inducible.…”
Section: Discussionmentioning
confidence: 99%
“…For target depletion experiments in undefined bacterial communities, three reared C57BL/6J mice were fed by 200 μL oral gavage in 20% ( w/v ) sucrose solution containing 10 9 CFUs of log-phase wild-type E. coli MG1655. Following ingestion of the bacterial suspension, the mice were provided with both standard rodent food and sterilized water.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, drawing inspiration from natural biofilms, self-repairing living biomaterials with cell-cell adhesion properties show regenerative capabilities and display improved resilience 5,7 . Furthermore, engineered intercellular adhesion could have profound impacts on targeted manipulations within complex microbial populations, enabling precise and efficient interventions against specific bacteria [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation